Treatment of Type I Endoleaks Using Transcatheter Embolization With Onyx. (February 2014) - Eberhardt, Karla Maria; Sadeghi-Azandaryani, Mojtaba; Worlicek, Stefanie; Koeppel, Thomas; Reiser, Maximilian F.; Treitl, Marcus
Purpose: To report a single-center experience with transcatheter embolization of type I endoleaks using the liquid embolic agent Onyx, an ethylene vinyl alcohol copolymer. Methods: Eight patients (4 men; mean age 74.8 years, range 63–86) with 10 type I endoleaks (6 abdominal and 4 thoracic) diagnosed 2 days to 9 years after endovascular repair were treated with Onyx embolization because cuff extension was precluded by an insufficient landing zone in 6 cases and an unsuitable aortic diameter in 2. Endoleaks were accessed with a 4-F diagnostic catheter and a coaxially introduced dimethylsulfoxide-compatible microcatheter. Onyx-34 was predominantly applied due to its high viscosity; patent side branches were coil embolized prior to Onyx delivery in 3 cases. Results: Technical success of the procedure was achieved in all cases. The mean volume of Onyx used for abdominal endoleaks was 11.8 mL (range 3.0–25.5) and 19.4 mL (range 4.5–31.5) for thoracic endoleaks. The average duration of the procedure was 76.7 minutes (range 34.5–110.6), and the average radiation dose area product was 18.8 cGy*cm 2 (range 10.6–55.8). Reperfusion of the endoleak was detected in one case 2 days after the procedure. A second case showed an occluded endoleak but a small trace of contrast between the aortic wall and the stent-graft. Non-target embolization was not found in any case. Mean follow-up was 13.2 months (range 8–24). The mean reduction in diameters for thoracic aneurysms after 6 and 12 months was 0.4 and 0.9 cm, respectively, and 0.6 and 1.2 cm, respectively, for abdominal aneurysms. Conclusion: Transcatheter embolization of type I endoleaks using Onyx is a simple, safe, and sustainable treatment option with a high primary success rate for cases in which stent-graft extension is not possible. The benefit of additional coil embolization remains uncertain.